Analysis of the Influence of Empowering Leadership and Organizational Culture Through Work Satisfation on Performance in the Office of the Regent of Enrekang - Mutmainnah, Mutmainnah; Jam’an, Andi; Rusydi, Muhammad (Journal of Public Representative and Society Provision, 2025)
The research aims to determine and analyze the influence of Empowering Leadership on job satisfaction, organizational culture on job satisfaction, Empowering Leadership on performance, organizational culture on on performance, job satisfaction on performance, empowering leadership through Job satisfaction on performance, and organizational culture through job satisfaction on performance on at the Enrekang Regent's Office. This study uses primary data and data collection through questionnaires and interviews. The data analysis method used is quantitative analysis, using SEM PLS (Partial Least Squares Structual Equation Modeling). The population in this study were all employees of the Enrekang Regent's Office as many as 115. The results of this study showed that empowering leadership has a positive and significant effect on job satisfaction, organizational culture has a posititive but not significant effect on job satisfaction,  empowering leadership has a negative and insignificant effect on performance,  organizational culture has a positif significant effect on job satisfaction, job satisfaction  has a positive and significant effect on performance, empowering leadership has a positive and significant effect on performance, empowering leadership has a positive and significant effect on performance through job satisfaction, and organizational culture has a positive but insignificant effect on performance through job satisfaction.